Synthesis of Substituted 1,2,4-Triazoles from Reaction of Nitrilimines with Substituted Hydrazones - M. Awadallah, Adel; S. Ferwanah, Abdel-Rahman; R. El-Haddad, Mehtab; Schrader, W. (Asian Journal of Chemistry, 2016)
Hydrazonoyl halides (1) react with substituted hydrazones of alkanone, cycloalkanone and heterocyclic ketones (2–4) to give the cycloaddition products 4,5-dihydro-1,2,4-triazoles (5–7). The assignment of structures (5–7) was based on spectral data (mass spectra, IR, 1H and 13C NMR).